2003
DOI: 10.1103/physreve.67.046402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of proton emission from 60-fs, 200-mJ high-repetition-rate tabletop-laser pulses interacting with solid targets

Abstract: Measurements of proton emission have been made from a variety of solid targets irradiated by a 60-fs, 200-mJ, 7 x 10(18)-W cm(-2) laser system operating at 2 Hz. Optimum target conditions were found in terms of target material and thickness. For Mylar targets of thickness 20-40 microm, a maximum proton energy of 1.5 MeV was measured. For aluminum targets, a maximum energy of 950 keV was measured for 12 microm, and for copper, 850 keV for 12.5 microm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…As a result, Al target foils with thickness greater than a few microns are usually employed to ensure that the ASE-pedestal does not induce an expansion of the target rear surface (Roth et al 2002). Using laser pulses with contrast of approximately 10 6 , for example, Spencer and co-workers (McKenna et al 2002;Spencer et al 2003) observed the highest proton energies from Al target foils of thicknesses of approximately 12 mm, with a sharp cut-off with thinner foils. With pulses of contrast better than 2!10 7 , Kaluza et al (2004) have shown that the optimum target thickness for proton acceleration decreases with the duration of the ASE-pedestal-with a minimum pedestal duration of 0.5 ns an optimum Al thickness of 2 mm was observed to produce protons with energies up to w3.5 MeV.…”
Section: Effects Of Laser Pulse Contrast On Ion Accelerationmentioning
confidence: 99%
“…As a result, Al target foils with thickness greater than a few microns are usually employed to ensure that the ASE-pedestal does not induce an expansion of the target rear surface (Roth et al 2002). Using laser pulses with contrast of approximately 10 6 , for example, Spencer and co-workers (McKenna et al 2002;Spencer et al 2003) observed the highest proton energies from Al target foils of thicknesses of approximately 12 mm, with a sharp cut-off with thinner foils. With pulses of contrast better than 2!10 7 , Kaluza et al (2004) have shown that the optimum target thickness for proton acceleration decreases with the duration of the ASE-pedestal-with a minimum pedestal duration of 0.5 ns an optimum Al thickness of 2 mm was observed to produce protons with energies up to w3.5 MeV.…”
Section: Effects Of Laser Pulse Contrast On Ion Accelerationmentioning
confidence: 99%
“…Previous investigations using medium contrast Ti: sapphire laser systems, 4,10 have demonstrated a gradual increase in maximum proton energy observed E max as the target thickness was decreased. For example, Kaluza et al with a laser contrast of 10 7 demonstrate an increase in proton energy with decreasing target thickness down to 2 m. The increase was attributed to reduced transverse spreading of the hot electrons inside the target.…”
mentioning
confidence: 99%
“…In the case of metal targets, Fuchs et al 34,35 have shown that in the intensity range of 10 18 -10 20 W / cm 2 , protons accelerated from the rear side of targets are dominant, which is well described by the isothermal plasma expansion model, 36 or target normal sheath acceleration ͑TNSA͒ model. Lee et al 37 have proposed a bulk acceleration model, or acceleration by a resistively induced electric field ͑ARIE͒ to account for more intense proton beams from plastic targets than those from metal targets [37][38][39] with a laser intensity lower than 10 19 W / cm 2 .…”
Section: Introductionmentioning
confidence: 99%